Kekuatan Tekan Beton Berpori Additive Sika Fume Mix Self Compacting Concrete - Adnan Adnan; Muh. Faridh Wajeni R; Mustakim Mustakim (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2023)
This research aims to determine the effect of adding the additive Sika Fume on the compressive strength of hollow concrete. This research uses a type of quantitative research with experimental methods, namely by carrying out several tests on test objects in the laboratory. The results of this research show that the compressive strength of hollow concrete with the addition of sika fume with a variation of 0% and 2% of the weight of cement, the experimental results obtained for the compressive strength of hollow concrete for 28 days of concrete with a variation of 0% with an average of 16.83 Mpa. For a variation of 2% with an average of 17.42 Mpa. So it can be concluded that concrete with a variation of 2% with an average of 17.42 Mpa is the variation with the highest compressive strength value and reaches the design compressive strength. Meanwhile, the 0% variation with an average of 16.83 Mpa is the lowest compressive strength value and does not reach the design compressive strength.